Policy actors' perceptions of obstacles to Sudan's policy of wheat self-sufficiency implementation. - Ahmed Ibrahim, Howida (Human Resource Management Academic Research Society (HRMARS), 2023)
Agriculture policies in Sudan have undergone various policy regimes targeted at improving productivity and food self-sufficiency. Policies play a vital role in setting priorities and actions for achieving food self-sufficiency as one of the food security strategies of the country. The objective of this study is to look into how policy actors perceived the implementation of the wheat self-sufficiency policy that aims to increase domestic production of wheat and decrease its imports. The findings of the study highlight several barriers to the effective implementation of the wheat self-sufficiency policy in Sudan's agricultural sector. These barriers were identified through interviews with 45 stakeholders representing various levels of government, farmers, industry representatives, and experts. The study employed thematic analysis to analyse the interview data. The main barriers to policy implementation identified by the policy actors are ineffective administrative measures, ineffective planning, technical risks, ineffective policy instruments, financial challenges, high production costs, ineffective governance, and foreign restrictions. The study, overall, suggests that the agricultural sector in Sudan faces significant challenges in implementing policies aimed at achieving wheat self- sufficiency. Addressing these barriers will require attention to administrative processes, improved planning, addressing technical risks, designing effective policy instruments, securing sufficient financial resources, reducing production costs, strengthening governance structures, and addressing foreign restrictions.